Pediatric Chronic Pain, Resilience and Psychiatric Comorbidity in Canada: A Retrospective, Comparative Analysis - Young, Megan A.; Anang, Polina; Gavalova, Anna (Frontiers in Health Services, 2022)
Objective Chronic pain compromises child and adolescent well-being and development. This study aimed to identify risk factors for chronic pain and exploration of how young people negotiate such risks and express resilience. We hypothesized children and youth with chronic pain would report greater prevalence of mental health disorders than the general population; and those demonstrating greater resilience would demonstrate less psychiatric comorbidity. Method A retrospective chart review was conducted for all patients (ages 7-17) attending the sole paediatric chronic pain clinic in Manitoba, from 2015-2019 (N = 116). Patients’ demographic information and psychiatric illness burden were compared to provincial epidemiological data using Chi-Square tests. Pain sites, family history, psychiatric illness, psychosocial functioning, treatment history and treatment recommendations were explored. Results The sample was predominantly female (74%; N = 114). 68% of patients reported a family history of chronic pain. 37% of the patients (vs. 14.0% anticipated; N= 326 260) reported comorbid psychiatric disorder, X2 (1, N = 114) = 53.00, p < .001. 32% reported diagnosis of mood and/or anxiety disorder (vs. 7.3%), X2 (1, N = 114) = 99.34, p < .001. Children and youth demonstrating resilience through engagement in more prosocial behaviours reported fewer psychiatric symptoms (rs = -.292, N = 114, p = .002, Spearman’s correlation). Conclusions Female sex, family history, and lower socioeconomic status were associated with chronic pain. Psychiatric conditions were more prevalent in chronic pain patients than in the general population. Approaching chronic pain from a mind-body perspective, while building on patients’ strengths, is central to informing treatment.